Coping Stress pada Remaja dan Orang Tua: Studi Kasus pada Kondisi Broken Home dan Anak Berkebutuhan Khusus - Alfita, Laili (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to determine Coping Stress in Adolescents and parents when facing problems. This study uses a comparative quantitative approach. The sample in the study amounted to 61 adolescents and 86 parents. The sampling technique was purposive sampling. The data analysis method used a comparative analysis with t-test statistical tests. The results of Data Analysis based on adolescent gender showed t = 2.718 with p = 0.009 < 0.050, while in parents the value of t = 1.003 with p = 0.319 > 0.050. Based on cross-tabulation in adolescents, it is known that those who use Coping stress; Emotion-Focused Coping in Adolescents: Out of 61 adolescents, 47 (77%) used Emotion-Focused Coping, with 23 males (37.7%), 24 females (39.3%), and 14 (22.9%) used Problem-Focused Coping. Furthermore, cross-tabulation of parents known to use Emotion-Focused Coping in 86 adolescents showed 81 (94.2%), with 41 mothers (50.6%) and 40 fathers (49.3%). Stress-Focused Coping was used by 5 fathers (5.8%).  Based on the data analysis, it can be concluded that there is no significant difference in Stress Coping between Emotion-Focused Coping and Problem-Focused Coping in adolescents and parents when dealing with problems.